EU Development Policies and the Socio-Economic Disadvantage of European Regions. - Riccardo Crescenzi (European Regional Science Association (ERSA), 2006)
The debate over the EU budget 2007-2013 made clear the need of an in-depth understanding of the distribution of the EU development funds. The scarce resources available need to be targeted more effectively towards the real needs of EU countries and regions in order to deliver the expected benefits. The literature on the impact of structural funds expenditure on regional growth and cohesion highlighted the reduced long-term impact of structural funds expenditure. One of the reasons for such result was identified in the biased allocation of funds among the different development axes. In this paper we assume a different perspective and focus the spatial structure of the expenditure for the Eu development policies under the 2000-2006 budget. For this purpose we collect a specific dataset for the EU-15 regions, including not only structural funds (as in the existing literature) but also rural development funds under the CAP. This extended dataset allows us to assess the spatial structure of a significant percentage of the total funds targeted towards regional development. On the basis such dataset we are able: a) to analyse the spatial concentration of structural expenditure as an important prerequisite for its effectiveness. A low degree of spatial concentration of the funds may support the hypothesis of a distribution based on political equilibrium rather than effectiveness. In addition we will be able to test the spatial association of rural and regional development funds which are rarely analysed jointly thus shedding some light on the spatial coherence of the expenditure for different policies; b) to compare the spatial concentration of EU funds with a specifically developed indicator of socio-economic disadvantage of the EU regions. This analysis will allow us to analyse the coherence of the EU regional policies with regard to the structural disadvantage of EU regions thus uncovering a potential inconsistency between policy objectives (favouring disadvantaged areas) and the beneficiaries of the funds. The paper shows that although there a certain degree of spatial association between structural and rural development expenditure the factors of socio-economic disadvantage are more spatially concentrated than the funds aimed at addressing such disadvantage.
Keywords: 330